2021
DOI: 10.3389/fbioe.2021.608150
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Sensitive Nanoparticles Co-delivering Dexamethasone and CDMP-1 for the Treatment of Osteoarthritis Through Chondrogenic Differentiation Induction and Inflammation Inhibition

Abstract: Objective: Osteoarthritis (OA) is a common subtype of arthritis. To date, treatment of OA focuses primarily on alleviating pain and improving joint function. The lack of a vascular system within synovial joints and the rapid removal of agents due to synovial exchange hinder continuous delivery of OA drugs. However, these obstacles are being addressed by promising nanoscale drugs.Methods: We synthesize and assemble a hydrogen peroxide [H2O2, belongs to the category of active oxygen species (ROS)]-sensitive nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…To synthesize PLGA-selenocystamine conjugates (LGsese), excess selenocystamine was reacted with PLGA and unreacted chemicals or byproducts were then removed by dialysis as reported by other researchers [ 32 , 33 , 34 ]. Specific peaks of PLGA were observed at 1.4~1.5 ppm and 4.6~5.4 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize PLGA-selenocystamine conjugates (LGsese), excess selenocystamine was reacted with PLGA and unreacted chemicals or byproducts were then removed by dialysis as reported by other researchers [ 32 , 33 , 34 ]. Specific peaks of PLGA were observed at 1.4~1.5 ppm and 4.6~5.4 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Fan et al, also reported that polymeric micelles composed of PLGA-PEG copolymer having diselenide linkages release berberine in a ROS-specific manner while berberine release in PBS was minimized [ 32 ]. Furthermore, it was reported that dexamethasone release from ROS-sensitive nanoparticles was accelerated in the presence of ROS due to the cleavage of diselenide linkages and this effectively inhibited the proliferation of activated macrophages [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“… [ 124 ] PLGA-SeSe-mPEG Dex and CDMP-1 ROS-responsive In vitro BMSCs; Raw264.7 The drug-loaded micelles effectively inhibited proliferation of activated macrophages, induced macrophage apoptosis with an anti-inflammatory effect, and caused the BMSCs to differentiate into chondrocytes. [ 123 ] LMWH-TOS Methotrexate Targeting inflammatory sites In vitro & vivo HUVECs; Mice The hydrophilic fragment low molecular weight heparin (LMWH) acts as a shield which block the transvascular movement of neutrophils through inhibiting the adhesion cascade by binding to P-selectin on inflamed endothelium; Hydrophobic fragment d-α-tocopherol succinate reduced matrix metalloproteinase-9, which was secreted by neutrophils and degrades the main components of articular cartilage; In collagen-induced arthritis (CIA) mouse model, LT NPs showed significant targeting effect, and exhibited prominent therapeutic efficacy after enveloping the first-line anti-RA drug methotrexate. [ 125 ] mPEG-PPF Ibuprofen pH-responsive In vitro HIG-82; Ibuprofen release was observed to increase with increasing acidic conditions and could be controlled by varying the amount of crosslinker used; Micelles exerted anti-inflammatory effects by significantly decreasing monosodium urate crystal-induced prostaglandin E2 levels in rabbit synoviocytes cultures in vitro.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…For example, the diblock copolymer poly (ethylene glycol)-block-poly (propylene sulfide) 122 and PLGA-SeSe-mPEG (poly (lactic-co-glycolic acid-SeSe-poly (ethylene glycol)) were used to modify micelles for ROS-sensitive drug delivery. 123 Considering that the folic acid (FA) receptor is highly expressed on arthritic macrophage membranes, FA-modified PSA (polysialic acid)-CC (natural cholesterol) micelles were developed to target macrophages in the synovial inflammatory microenvironment. 124 Conjugate polymers of heparin and d-α-tocopheryl succinate (LMWH-TOS) also reportedly target the inflammatory microenvironment.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Additionally, polymer micelles using ‐SeSe‐ group as the ROS‐responsive component have also been studied. [ 72 ] The polymer micelles contain both DEX and cartilage‐derive morphogenetic protein‐1, whose ‐SeSe‐ linkages are oxidized to break in ROS environment. The concentration of inflammatory factor and collagen II were measured by enzyme linked immunosorbent assay, showing suppression of TNF‐ α and IL‐1 β as well as upregulation of collagen II in drug‐loaded NPs co‐cultured cells.…”
Section: Stimuli‐sensitive Nanotherapies For Oa Treatmentmentioning
confidence: 99%